Minimalist, standard and no footwear on static and dynamic postural stability following jump landing - Zech, A.; Argubi-Wollesen, A.; Rahlf, A.-L. (European Journal of Sport Science, 2015)
In recreational sports, uncushioned, light-weight and minimalist shoes are increasingly used to imitate barefoot situations. Uncertainty exists whether these shoes provide sufficient stability during challenging movements. In this randomised crossover study, 35 healthy distance runners performed jump landing stabilisation and single-leg stance tests on a force plate, using four conditions in random order: barefoot, uncushioned minimalist shoes, cushioned ultraflexible shoes and standard running shoes. Ground reaction force (GRF) and centre of pressure (COP) data were used to determine unilateral jump landing stabilisation time and COP sway velocity during single-leg stance. Repeated measures analysis of variance revealed significant footwear interactions for medial-lateral (p < 0.001) and anterior-posterior COP sway velocity during standing (p < 0.001). The barefoot condition produced significantly greater postural sway velocities (p < 0.001) compared to all footwear conditions. No significant effects were found for jump landing stabilisation time. In conclusion, the results of this study indicate that increased shoe flexibility and reduced sole support have no, or only minor influence on static and dynamic postural control, and therefore, may not increase the risk of traumatic events during sports activities. However, barefoot conditions should be considered carefully when adequate postural control is needed.